Las maneras de medir en el pueblo asháninka - Jumanga Caballero, Jamer (2025)
This study details the measurement techniques that are performed daily in the Asháninka people under the direction of parents for a long period, whose current strategies are employed by students of the third cycle that enhance their mathematical skills. The objective is to establish the level of influenceof ethnomathematical activities in improving the development of numerical skills in Asháninka students of 8 and 9 years old of the Bilingual Educational Institution N° 30956. The methodology used is quantitative, descriptive, non-experimental design. The population consisted of 86 students and thesample consisted of 22 students. The findings obtained were favorable, since through a descriptive analysis it was established that the students increased their level of numerical skills. This was evidenced because the mean in a pretest of 5.68 showed an improvement of 7.5 in the mean. Similarly, 21 of thestudents were in a positive range with a bilateral significance of 0.000, accepting the alternate hypothesis.